Pembentukan Bintil Akar dan Ketahanan Beberapa Aksesi Kacang Hijau (Vigna radiata L.) Pada Kondisi Salin - Panji Catur Anugrahtama; Supriyanta Supriyanta; Taryono Taryono (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2020)
Salinity or high salt content in the soil became one of the environmental factors that can threaten the sustainability of mungbean in the ield because mungbean is considered as a salinity-sensitive plant. Therefore, it is necessary to develop cultivars that are saline stress tolerance. This study aims to determine the effect of salinity on mungbeans growth and classify the salinity tolerance levels of 16 mungbean accessions and associate the level of salinity tolerance to the formation of root nodules. Comparisons were made by growing mungbean under normal conditions and treated with salinity stress by watering 500 ml of 200 mM NaCl solution every seven days from the age of 21 days after planting. The observations have made on both the vegetative and generative phases of plants. Data were analyzed using analysis of variance, deining levels of salinity stress tolerance based on analysis of salinity sensitivity index values. The results showed that several mungbean accessions made adjustments to the stres environment by reducing growth and yield components. Based on the Scott-Knott test and the values of the salinity sensitivity index found that several mungbean accessions possess tolerance to salinity stress at soil EC reaching 2,73 dS/m. Accessions that are potential as a genetic source of salinity tolerance showed by accessions number 1, 4, 8, and 19. Accessions number 1, 8, and 19 that classiied as salinity tolerance have higher ability to form nodules rather than nontolerance accessions at saline conditions.